(untitled) (European Journal of Education and Psychology, 2018)
This study analyses the relationship between resilience, dispositional optimism and academic burnout dimensions (exhaustion, cynicism and reduced academic efficacy). A sample of 463 students from Universidad de León was evaluated. The following assessment instruments were employed: Maslach Burnout Inventory-Student Survey (MBI-SS), Connor-Davidson Resilience Scale (10-item CD-RISC) y Life Orientation Test Revised (LOT-R). The results showed that academic burnout is significantly related to resilience and optimism. In particular, resilience is significantly and positively related to efficacy whereas optimism is positively related to efficacy but negatively related to exhaustion. Moreover, it was found that resilience predicted efficacy while optimism predicted exhaustion. However, cynicism was no related to resilience nor to optimism. Finally, implications for prevention programs design are proposed.